Pengaruh Adopsi Cloud Accounting Terhadap Kinerja UKM: Studi Kasus Multi-Perusahaan di Sektor Ritel - Napitupulu, Merry Anna; Siahaan, Septony Benyamin (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Digital transformation requires Small and Medium Enterprises (SMEs) in the retail sector to adopt innovative technologies, one of which is cloud accounting. This study aims to analyze the effect of cloud accounting adoption on SME performance, both from financial and non-financial aspects. Using a multi-enterprise case study method, this research involved eight retail SMEs in three major Indonesian cities. Data were collected through interviews, observations, and document analysis, and then analyzed using an interpretive approach. The results showed that cloud accounting improved operational efficiency, financial reporting accuracy, and strategic decision-making. Financially, SMEs experienced a 17.3% decrease in average operating costs and an 8.2% increase in Return on Investment (ROI). Key factors for successful implementation include management commitment, employee training, and digital infrastructure readiness. This study recommends strategies to optimize cloud accounting adoption so that SMEs can be more adaptive to market changes and improve business competitiveness.